ADVANTAGES OF USING “BLENDED LEARNING” (FLIPPED CLASSROOM) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the essence and advantages of using the “Blended Learning” in the modern educational process. In this method, students study the lesson materials independently in advance, and during class sessions they focus on practical tasks, discussions, and group work. The article emphasizes that this technology serves to increase student activity, enhance the effectiveness of the lesson process, use an individual approach, effectively use digital technologies, and develop creativity and critical thinking. The conclusion highlights the contribution of this innovative approach to improving the quality of education.